Legal basis for electronic document management in the tax authorities system in our country - Ashirov Jamolbek Shuxrat o‘g‘li (Genius Journals, 2024)
Today, within the framework of the tax administration, optimization of the structure of taxes, their collection, improvement of the mechanism of tax accounting and reporting, correct calculation of taxes, timely and full payment, the right of taxpayers established in the tax legislation and monitoring compliance with obligations, distribution of tax revenues between budgets of different levels, collection and analysis of results, implementation of extensive measures to harmonize tax relations of all participants in the taxation process are being conducted . Also, to ensure the implementation of the priority tasks set within the framework of the open dialogue of the President with entrepreneurs held on August 18, 2023, as well as more favorable conditions for business entities that pay taxes on time and operate in accordance with legal requirements. in order to create conditions and encourage them, by introducing digital technologies to the tax administration, expanding the tax base and some important reforms implemented in the tax system are studied, foreign experience, scientificpractical conclusions and suggestions on its application in our country are developed developed.
Keywords: stability rating; business entities; fiscal policy; crisis